The Influence of Perceived University Support and Proactive Personality In Explaining Entrepreneurial Intentions Among University Students The Case of University of Nottingham, Malaysia Campus - Chee, Lai Kei (2015)
This study explores the relationship between the proactive dimension of personality and perceived university support toward entrepreneurial intentions among undergraduate university students in the University of Nottingham, Malaysia campus. This study proposes and tests a multi-perspective and integrative framework. I have hypothesized that the three facets of perceived university support, that is, perceived educational support, perceived concept development support and perceived business development support together with the proactive personality of students, constitute motivations in students’ intention to start a business venture. A sample of 141 undergraduate students participated in the study and data were analysed using hierarchical multiple regression analysis. The findings suggest that students’ proactive personality indicates an incremental effect on intentions and adding it to the university support would greatly increase the formation of students’ entrepreneurial intention, however, perceived educational support and perceived business development support gave insignificant contribution towards the model. Theoretical and practical implications are discussed.